Correlation Between the Acoustic and Cell Morphology of Polyurethane/Silica Nanocomposite Foams: Effect of Various Proportions of Silica at Low Frequency Region - Marziye Pirani; Mohammad Raza Monazzam; Seyed Qasem Pourjandaghi (بهداشت و ایمنی کار, 2021)
Introduction: Reducing noise pollution has become an essential issue due to the increase in public concern and also social demands for a better lifestyle. Using sound absorption materials is a preferred method to reduce the noise pollution. Undesirable properties of pure polyurethane such as poor absorption of mechanical energy in narrow frequency ranges can be improved by providing polymeric nanocomposites.  The main purpose of this study is to synthesize the polyurethane nanocomposite foams in order to improve its acoustic properties. Material and Methods: At the first steage, pure polyurethane foam was synthesized using the pre-polymer method. Afterwards, nanocomposite foams were synthesized with different mass fractions of Nano silica. The cellular morphology of prepared nanocomposite foams was investigated by scanning electron microscopy (SEM (.Utilizing a  two-microphone impedance tube,  sound absorption coefficient (α) was calculated in the frequency ranges of 100 Hz to 1600 Hz in order to investigate the acoustic properties of the new absorbant. Results: According to the microscopic investigations, morphology of the cells changed after adding silica nanoparticles. Also, the cell sizes were observed to be decreased by increasing the amount of silica nanoparticles. Furthermore, the acoustic analysis of nanocomposite foams indicated that the sound absorption increased by enhancing the load of silica nanoparticles. Conclusion: In the current study, the effect of silica nanoparticles additive amount on acoustic properties of the polyurethane-based nanocomposite was investigated. Our findings depicted that the polyurethane-based nanocomposites were able to promote the sound absorption coefficient.